Extreme drought stress shifts net facilitation to neutral interactions between shrubs and sub‐canopy plants in an arid desert. Issue 3 (4th December 2017) - Zhang, Gefei; Zhao, Wenzhi; Zhou, Hai; Yang, Qiyue; Wang, Xiaofen
Abstract : The stress gradient hypothesis (SGH) predicts that the importance or intensity of competition and facilitation will change inversely along abiotic stress gradients. It was originally postulated that increasing environmental stress can induce a monotonic increase in facilitation. However, more recent models predicted that the relationship between severity and interaction exhibits a hump‐shaped pattern, in which positive interactions prevail under moderate stress but decline at the extreme ends of stress gradients. In the present study, we conducted a field experiment along a temporal rainfall gradient for five consecutive years, in order to investigate interactions in a shrub‐herbaceous plant community at the southern edge of the Badain Jaran Desert, and, more specifically, investigated the effects of Calligonum mongolicum, a dominant shrub species, on both abiotic environmental variables and the performance of sub‐canopy plant species. We found that shrubs can improve sub‐canopy water regimes, soil properties, plant biomass, density, cover, and richness and, more importantly, that the positive effect of shrubs on sub‐canopy soil moisture during the summer diminishes as rainfall decreases, a pattern that partly explains the collapse of the positive interaction between shrubs and their understory plants. These results provide empirical evidence that the positive effect of shrubs on understory plant communities in extreme arid environments may decline and become neutral with increasing drought stress.